Assessing English Language Textbooks: Analysing Task/Learning Activities In Bahasa Inggris SMP/MTs Kelas IX Semester 1 - Pratama, Dimas Riezky (Peneliti.net, 2024)
The utilization of an English textbook serves a dual purpose, acting not only as a guiding tool for educators during lesson delivery but also as a conduit for essential input through diverse explanations and interactive exercises. This dynamic also exerts an influence on learners' dispositions and performance towards the instructional materials. This intricate scenario has motivated the author to embark on a research-oriented endeavour, focusing on the evaluation of textbooks. The aim is to scrutinize the tasks within the English textbook context, particularly in senior high school settings, encompassing their complexity progression. The outcomes of this study underscore that the English textbook titled